Effect of Ultrasonic Marination on Broiler Breast Meat Quality and Salmonella Contamination - Smith, D.P. (International Journal of Poultry Science, 2011)
Two experiments were conducted to determine the effect of ultrasonic or static marination on meat quality measures (marination uptake, drip loss cooked yield and texture) and reduction of Salmonella and Escherichia coli. In experiment one, twelve butterfly fillets per each of two trials (n = 24) were collected from a commercial processing plant and trimmed of connective or fat tissue, then cut into paired fillets. One fillet from each pair was assigned to marination either with ultrasonication or without (static) for 20 min in a solution containing 91% water, 6% NaCl and 3% Sodium Tripolyphosphate (STP). Fillets were weighed, held for 18 h, cooked and analyzed for texture using Allo-Kramer shear. Sonication resulted in lower uptake (2.6%), less drip loss (1.1%) and lower cooked yield (84.3%) than static marination (4.8, 2.2 and 88.7%, respectively); there was no difference in shear due to marination method (3.4 vs. 3.7 kg/g). In experiment two, 4 trials were conducted to determine the effect of marination method on numbers of Salmonella and Escherichia (E.) coli. In each trial, two whole boneless (butterfly) skinless broiler breasts were obtained from a retail store and split into paired fillets (n = 8). Ten min prior to marination fillets were inoculated with 1.0 ml of a culture containing nalidixic acid-resistant strains of Salmonella (mean count of 7.1 log10) and E. coli (mean count of 6.1 log10). After marination fillets were sampled for bacterial enumeration. There were no significant (p